2009
DOI: 10.1177/172460080902400406
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of urine telomerase activity to detect bladder cancer in symptomatic patients

Abstract: Telomerase activity assessment in voided urine is an important noninvasive tool for bladder cancer diagnosis. In a previous case-control study we verified that this method can detect tumor cells in urine with high sensitivity and specificity, but few data are still available on its accuracy to detect tumors in patients with symptomatic urinary tract diseases. Following recently published guidelines on bladder cancer, we aimed to define the diagnostic accuracy of urine telomerase levels in symptomatic patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Cytology test is very specific (a positive result is highly indicative of bladder cancer) but suffers from low sensitivity (a negative result does not exclude the diagnosis of cancer, particularly for cancer at first stages); comet test is able to identify early DNA damage that could increase the risk of cancer and TRAP analysis seems to be able to sensitively detect telomerase activity levels in superficial urothelial cell carcinoma [15, 18, 26]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cytology test is very specific (a positive result is highly indicative of bladder cancer) but suffers from low sensitivity (a negative result does not exclude the diagnosis of cancer, particularly for cancer at first stages); comet test is able to identify early DNA damage that could increase the risk of cancer and TRAP analysis seems to be able to sensitively detect telomerase activity levels in superficial urothelial cell carcinoma [15, 18, 26]. …”
Section: Discussionmentioning
confidence: 99%
“…Other urinary biomarkers such telomerase activity (TA) levels by Telomeric repeat amplification protocol (TRAP) assay [18, 19], DNA damage in exfoliate urinary cells by comet assay [20], and DNA methylation markers are being investigated [16] and seem to be good candidates for early detection of bladder cancer. However these biomarkers require being validated in further studies on subjects at risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…

The first one, telomeric repeat amplification protocol (TRAP) assay , uses PCR amplification of a telomeric template with posterior analysis by ELISA or RT-PCR. This assay needs at least 50 copies of telomerase-expressing cells to have positive results, so the false negatives are something relatively frequent [47].

The second one, human telomerase reverse transcriptase (hTERT) assay , measures the messenger RNA levels of the catalytic subunit of the telomerase by RT-PCR [47].

…”
Section: Telomerase As Cancer Marker: Urine Biomarkermentioning
confidence: 99%
“…Telomerase activity assessment in voided urine is an important noninvasive tool for detection, diagnosis and follow-up of human bladder cancer. Casadio et al verified that Telomerase activity assessment can detect tumor cells in urine with high sensitivity and specificity (Casadio et al, 2009). They evaluated the urinary telomerase activity of 515 patients, and found that the overall accuracy, in DOI:http://dx.doi.org/10.7314/APJCP.2012.13.5.1723 Potential Urinary Markers in the Early Detection, Diagnosis andFollow-up of Human Bladder Cancer terms of true positives and true negatives, was 80%.…”
Section: Telomerasementioning
confidence: 99%